Modern Forms of Employment - Dadajonova Martabokhon Mahmudovna (Universitas Muhammadiyah Sidoarjo, 2022)
In this article are analyzed the possibilities of using modern forms of employment in the country, and also develops recommendations for regulating distance employment, which is relevant in modern conditions.